USE OF MARKETING TECHNOLOGIES IN THE DEVELOPMENT OF MODERN SHOPS IN VILLAGES AND CITIES AND INCREASING THE CULTURE OF SERVICE IN THEM (Marketing Journal, 2025)
The article discusses the features of retail trade, the development of modern retail outlets in rural and urban areas, ways to improve the culture of modern trade and the provision of services in them based on digital marketing technologies.
Keywords: trade; retail; marketing; digital marketing technologiyes; retail outlets; retail chains; trade infrastructure; retail enterprises; competitiveness; trade entities; trade culture